Mis Boon: Daughters of the Horn - Abdulrahman, Feyrouz (Canada, 2006)
This short documentary tells the history of Eritrea through the stories of young Eritrean women living in Canada. Nearly 20 years after the Eritrean declaration of independence, the women gather over the traditional coffee making ceremony (mis boon) to discuss their thoughts and experiences as young Eritreans.
Verzio Film Festival Submission
Duration: 00:23:00
Verzio Film Festival Submission
Keywords: Documentary films